1980
DOI: 10.3109/10826088009040011
|View full text |Cite
|
Sign up to set email alerts
|

Drug Histories and Criminality: Survey of Inmates of State Correctional Facilities, January 1974

Abstract: In January 1974, the Law Enforcement Assistance Administration, assisted by the Census Bureau, interviewed 10,400 inmates of state correctional facilities. Results from this survey were applicable to 191,400 inmates, which was the estimated population of all state correctional facilities at the time of the survey. Findings showed that an estimated 61% of the 191,400 inmates stated they had used drugs such as heroin, methadone, cocaine, marijuana, amphetamines, or barbiturates at some point in their lives, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…There were a number of other reasons for exclusion: (1) failure to include the whole prison population or a random sample of this population [34–36]; (2) reporting of retrospective substance use while in prison in post‐release prisoners [37,38]; (3) reporting estimates from only prisoners selected for assessment or treatment of substance dependence [39,40]; (4) reporting of combined results for men and women [10]; (5) reporting of combined estimates for alcohol and drug misuse [41,42]; (6) greater than 50% non‐participation [43]; (7) measuring solely injectable substance use [36,39,44]; and (8) lack of standardized criteria or unclear definitions regarding either substance abuse or dependence [35,45–65]. A group of studies examining the prevalence of drug dependence as part of the Arrestee Drug Abuse Monitoring programme in the United States was excluded for this latter reason [13,14]; (9) one 1985 study that used diagnostic criteria according to the International Classification of Diseases, version 8 [66].…”
Section: Methodsmentioning
confidence: 99%
“…There were a number of other reasons for exclusion: (1) failure to include the whole prison population or a random sample of this population [34–36]; (2) reporting of retrospective substance use while in prison in post‐release prisoners [37,38]; (3) reporting estimates from only prisoners selected for assessment or treatment of substance dependence [39,40]; (4) reporting of combined results for men and women [10]; (5) reporting of combined estimates for alcohol and drug misuse [41,42]; (6) greater than 50% non‐participation [43]; (7) measuring solely injectable substance use [36,39,44]; and (8) lack of standardized criteria or unclear definitions regarding either substance abuse or dependence [35,45–65]. A group of studies examining the prevalence of drug dependence as part of the Arrestee Drug Abuse Monitoring programme in the United States was excluded for this latter reason [13,14]; (9) one 1985 study that used diagnostic criteria according to the International Classification of Diseases, version 8 [66].…”
Section: Methodsmentioning
confidence: 99%
“…As in studies of known drug abusers, the use of arrest data to classify criminal justice subjects has obscured the relationship between illicit drug use and involvement in serious crime. Classifying subjects according to the arrest charge for the crime for which they were most recently incarcerated, Barton (1980Barton ( , 1982 reported that the prevalence of both lifetime and regular drug use was higher among property offenders than among violent offenders. The results of recent studies using other ways of classifying subjects, however, have challenged the view that arrested drug users are less violent than other arrestees.…”
Section: Drug Use Of Individuals In the Criminal Justice Systemmentioning
confidence: 99%
“…Barton's (1976) analysis of LEAA national prison survey data provides an important set of preliminary findings. Barton indicates that 61 percent of incarcerated offenders self-report some ill egal drug use activity and 13 percent claim to have used heroin at the time of the arrest leading to imprisonment.…”
Section: Simple Drugs and Crime Associationsmentioning
confidence: 99%